Baihe Dihuang Tang as a therapeutic candidate for insomnia: Targeting gut dysbiosis and neuroendocrine dysfunction - Chu, Liuxi; Lu, Qin; Chen, Pingping; Feng, Zunyong; Wu, Ping; Shen, Jiamen; Jiang, Yi; Yang, Yang; Tan, Xiran; Wang, Xiaomeng; Deng, Guoxing; Wang, Xi; et al. (iMetaOmics (Print), 2025)
Baihe Dihuang Tang (BDT), is a traditional Chinese medicinal formulation historically utilized to manage various health conditions, including insomnia. This therapeutic use of BDT for treating insomnia is rooted in its potential to regulate the gut microbiota, neuroendocrine, and serotonin systems, which may collectively contribute to its effectiveness. This study aims to explore the anti‐insomnia effects of BDT, and focus on its underlying mechanisms, emphasizing the potential interplay with gut microbiota, neuroendocrine, and serotonin pathways. An insomnia mouse model was induced using p‐chlorophenylalanine (PCPA). Subjects received varying doses of BDT or a saline solution as a control. Behavioral assessment was conducted via the open field test and elevated plus maze test. Hypothalamic monoamine neurotransmitter levels were quantified using ELISA kits. Neurosteroid levels in brain and serum samples were determined through high‐performance liquid chromatography‐tandem mass spectrometry (HPLC‐MS/MS). Gut microbiota composition was evaluated using 16S rRNA amplicon sequencing. PCPA‐induced insomnia led to significant alterations in neurosteroids, monoamine neurotransmitters, and gut microbiota composition. BDT treatment markedly improved behavioral parameters in insomniac mice, evidenced by enhanced motility and reduced sleep latency compared to controls. BDT administration restored neurosteroid and monoamine neurotransmitter dose‐dependently, suggesting potential for neuroendocrine system homeostasis restoration. BDT‐treated mice exhibited significant gut microbiota composition changes, including reduced Acidobacteria, increased Fusobacteria and Firmicutes at the phylum level, and decreased Alistipes at the genus level, compared to the insomnia model group. BDT effectively rectifies gut dysbiosis and mitigates neuroendocrine and serotonin system dysfunctions induced by insomnia, emerging as a promising therapeutic candidate for insomnia management. In this study, we utilized a PCPA‐induced insomnia mouse model to investigate the therapeutic effects of Baihe Dihuang Tang (BDT) on sleep disorders. Our findings indicate that BDT treatment effectively reshapes the dysregulated gut microbiota, characterized by a decrease in Acidobacteria and an increase in Fusobacteria and Firmicutes at the phylum level. Additionally, BDT treatment restores the abnormal levels of neurotransmitters in various brain regions and corrects the hormonal imbalances observed in peripheral blood. Behavioral assessments demonstrated marked improvements in locomotion and reduced sleep latency among BDT‐treated mice compared to the insomnia model group. These results highlight the potential of BDT as a promising therapeutic agent for insomnia, suggesting that its multifaceted mechanisms may involve the modulation of gut microbiota and restoration of neuroendocrine and serotonin system functions. Overall, our findings provide compelling evidence supporting BDT's role in the management of insomnia, paving the way for further exploration in clinical applications. Highlights This study demonstrates that Baihe Dihuang Tang (BDT) effectively corrects gut dysbiosis linked to insomnia, suggesting its potential to improve sleep quality through microbiota regulation. BDT shows the ability to normalize neurosteroid and monoamine neurotransmitter levels in hypothalamus, indicating its multifaceted effects on neuroendocrine dysregulation in sleep disorders. The observed improvements in locomotion and reduced sleep latency in insomniac mice treated with BDT highlight its comprehensive therapeutic potential for addressing both behavioral and biochemical factors of insomnia.